Partners for excellence: Committed to meaningful partnerships with patients and families in pediatrics - Rachel Biblow, MSW; Sara Toomey (The Beryl Institute, 2018)
Although the landscape in pediatrics continues to shift and change, one of the keys to our continued success remains the same... it's about partnership. It's clear the element of partnership is well woven through our organizations as illustrated by many of us having patient and family advisory councils, family consultants, and family partners. While this foundation is strong and essential, we must do more to truly listen, recognize the value of patient and family involvement, act upon the information shared, openly discuss issues, and strive for better together. True partnership with patients and families requires us to shift the paradigm even further by incorporating and ensuring that patients and their families are included in all aspects of our organizations - from the design of care plans, to system changes and improvement efforts, to participation on hospital committees and being recognized as the partners and thought leaders. We should recognize that patients and their families have the greatest skin in the game and will help us accelerate the advancements.